ANTI-ULCER AGENTS: A PHARMACOLOGICAL UPDATE OF THE PAST TEN YEARS - SUDIP KUMAR MANDAL,; SUBHOJIT DAWN,; ANINDYA BOSE, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
New anti-ulcer substances are still vitally necessary for the people of countries such as India and South Africa to avoid high cost of the most prescribed marketed anti-ulcer drugs (proton-pump inhibitors). New candidate against gastric ulcer is also necessary to avoid the potential problem (enterochromaffin-like cell hyperplasia may be induced) associated with the long-term use of synthetic proton-pump inhibitors. However, the search for the novel entity against ulceration is challenging because of the complexity of the ulcer process and its role in host defense to infections. Nature is the source of remedies for the humankind. Among the different biological activities of the natural products that have been published till date, anti-ulcer is one of the most reported effects. Some single natural products such as curcumin, 1-hydroxy-3,7,8-trimethoxyxanthone, cinnamic acid, thymol, epoxycarvone, and menthol; single synthetic products such as, 4,6-diaryl-3, 4-dihydropyrimidin-2(1H)-thiones, 1,4-dihydropyrimidine derivatives, and dihydropyrimidinone and piperidine hybrids; plant products such as Aloe vera, Mangifera indica, Zingiber officinale, Azadirachta indica, Psidium guava, Carica papaya, Panax ginseng, Terminalia chebula, Ocimum sanctum, Daucus carota, and Mimosa pudica, Alpinia galangal; nutraceuticals such as garlic, cauliflower, banana, honey, cucumber, and cod liver oil with anti-ulcer effects have been discussed in this review. A complete review of literature was conducted using different databases on ScienceDirect, Scopus, PubMed, and Google Scholar. This review is a genuine attempt to explore the past 10 years’ pharmacological update of some anti-ulcer agents.